Ambulatory Psychophysiology and Ecological Validity in Studies of Sports Performance: Issues and Implications for Intervention Protocols in Biofeedback - Carlstedt, R. A. (Biofeedback, 2001)
The heart activity of an elite tennis player was monitored over the course of two complete official tournament tennis matches to determine whether trends in heart rate deceleration observed in the laboratory and in more static sports would occur in an action sport. Consistent with previous research heart rate deceleration was evident prior to action phases of both matches. Greater magnitudes of heart rate deceleration also occurred in a match that was won compared to one that was lost. This study differed from previous ones in that heart activity was analyzed in the context of a realistic and more ecologically valid situation (entire real matches) and a meaningful longitudinal dependent measure of performance (match outcome). Since heart rate deceleration has been associated with attention, cognitive activity, and physiological reactivity, the author proposes that heart activity may be the measure of choice for assessing psychological and behavioral states in athletes and for concurrently validating or evaluating the efficacy of performance enhancement interventions including neurofeedback in real life competition, something that may be critical for the credibility and long-term viability of biofeedback in sport and performance psychology.